Integrating Islamic Values into Environmental Education: A Sustainable Eco-Pesantren Strategy - Habib Zainuri (Yayasan Indonesia Emerging Literacy Education, 2026)
This study examines how Islamic values can be integrated into environmental education to strengthen pesantren as sustainable Islamic educational institutions. Using a narrative literature review, the article synthesizes scholarly works on Islamic education, environmental ethics, eco-pesantren, and sustainable development. The review was conducted through transparent procedures covering database searches, keyword selection, inclusion and exclusion criteria, thematic coding, and content analysis. The findings reveal four interrelated themes: Islamic ecological ethics as a theological foundation, pesantren as an institutional ecosystem for value internalization, curriculum and hidden-curriculum strategies for ecological learning, and community-policy collaboration for developing eco-pesantren. The discussion shows that pesantren-based environmental education aligns with modern environmental education theory while adding a distinctive spiritual dimension rooted in khalifah fi al-ard, amanah, the prohibition of israf, tazkiyah al-nafs, wasathiyah, and rahmatan lil alamin. The article contributes a faith-based eco-pesantren strategy that connects Islamic values, pedagogical practices, institutional culture, and sustainable development goals. This strategy positions pesantren not only as religious learning centers but also as transformative institutions for ecological awareness and environmental responsibility.